A POLICY DEVELOPMENT FOR TRANSFORMING ACCESS TO EDUCATION: DIGITAL INFRASTRUCTURE DEVELOPMENT, ADAPTIVE LEARNING PLATFORMS, AND DIGITAL LITERACY INITIATIVES IN RURAL COMMUNITIES - Yundri Akhyar; Eli Sutrawati (Inteligensi : Jurnal Ilmu Pendidikan, 2026)
Educational inequality between rural and urban areas remains a global challenge, driven by disparities in digital infrastructure, access to technology, and digital literacy. Rural schools often face limited internet connectivity, insufficient technological resources, and low digital competencies among teachers and students, restricting effective digital learning implementation. This study aims to develop a policy framework to improve educational access in rural communities through adaptive learning platforms and digital literacy initiatives. Using a policy-oriented conceptual approach, the study reviews literature and international frameworks on digital education, technology adoption, and the digital divide. Three key policy dimensions are identified: digital infrastructure development, adaptive learning technology integration, and digital literacy enhancement. Findings show that digital infrastructure is the foundation of technology-based education, while adaptive learning platforms create personalized and flexible learning environments that improve engagement and accessibility. Digital literacy initiatives are essential for effective technology use among teachers and students. The study proposes an integrated policy model combining these dimensions to reduce the rural–urban education gap and support inclusive digital learning ecosystems. The framework provides practical guidance for policymakers, educational institutions, and technology stakeholders in implementing sustainable digital education strategies in rural areas.